The Implications of Complexity for Development - Barder, Owen (2012)
In this lecture, adapted from his May 2012 Kapuściński Lecture, Owen B arder explores the implications of complexity theory for development p olicy. He explains how traditional economic models have tried and fail ed to understand why some countries have managed to improve living sta ndards while other countries have not.
Keywords: IMPORTANT